ACTIVITY SALIVARY BACTERIA OF ACUTE LYMPHOBLASTIC LEUKEMIA CHILDREN IN CHEMOTHERAPY PHASE - Muthalib, Aliyah Abdul; Sarworini B.Budiardjo; Suharsini, Margaretha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to investigate the differences activity of salivary Streptococcus mutans bacteria in children suffer acute lymphoblastic leukemia (ALL) in phase of chemotherapy, induction, intensification/consolidation, and maintenance. Methods: This study was a laboratory observational, and cross-sectional method, conducted 19 ALL children in phase of chemotherapy, induction, intensification/consolidation, and maintenance. 2 mm of dental plaque was collected from mesiobuccal first permanent molar and incubated for 48 h at 37Â°C, and the bacterial activity of S. mutans measured by Cariostat. Results: Odds ratio analysis among chemotherapy phase of induction, intensification/consolidation, and maintenance is not significant (p>0.05) differences. Conclusion: The highest activity bacteria of S. mutans were found in the induction phase